ANALISIS DAYA DUKUNG LAHAN PERTANIAN PANGAN DI KABUPATEN TANAH DATAR TAHUN 2002-2018 - Elma liana; iswandi U (JURNAL BUANA, 2019)
The purpose of this research is to know the dynamics of changes in paddy fields and carrying capacity of agricultural land in Tanah Datar District in 2002 - 2018. It is a quantitative descriptive study. Using the supervised classification method, and the formula for comparing the area of harvest of food crops per capita with the area of land for food self-sufficiency. Results: 1) The area of paddy fields in the Tanah Datar districts in 2002 - 2018 was reduced by 4189 Ha. 2) Class I self-sufficiency areas in Tanah Datar District were eight sub-districts in 2002, namely Batipuh, Batipuh Selatan, , Pariangan, Tanjung Emas, Lintau Buo, Salimpaung and Tajung Baru Districts. In 2010 there were 3 additional districts of Lintau Buo Utara, Sugayang and Padang Ganting, in 2018 an increase in 1 Rambatan District. Regional food self-sufficiency classes II, namely Lintau Buo District, Lima Kaum and X Koto.